Upper-Limb Entheses in Healthy Children: A Comprehensive Ultrasound Study. (September 2021) - Martire, María Victoria; Collado, Paz
Abstract : Background: Interest in ultrasound (US) as a diagnostic tool in spondyloarthritis is growing. Although the literature has provided detailed description of normal lower-limb entheses for adults and children, validated normal US findings of the pediatric upper-limb (UL) entheses are lacking. Objectives: The aim of this study was to describe the sonographic characteristics of the UL entheses in healthy children to provide a basis for assessing pathologic findings in children with rheumatic diseases. Methods: This is an observational, cross-sectional study. The recruited healthy children were grouped according to age: group 1, 3–9 years (n = 22); group 2, 10 to 13 years (n = 12); and group 3, 14 to 18 years (n = 9). The following UL entheses were examined: (1) supraspinatus, (2) common flexor, (3) common extensor, and (4) triceps. Ultrasound examination was performed in B mode for morphology and structural abnormalities, and power Doppler was applied to detect vascularization within the enthesis and cartilage sites. Results: Forty-three children with a median age of 9 years (6–13 years) were included; 55% were boys. A total of 344 entheses were evaluated; all of them presented a homogeneous hyperechoic fibrillar pattern. Tendon insertion thickness at the bone attachment site increased with age and was greater in males. No signs of chronic enthesopathy were detected. Doppler signal was observed in children from groups 1 and 2, but not in any of the patients in group 3. In group 1, intraentheses signal was detected in the common extensor tendon insertion as an isolated signal (n = 2 patients), whereas intracartilage signal was detected in the supraspinatus (n = 1 patient) and the triceps (n = 1 patient). In group 2, intracartilage signal was detected in the common extensor (n = 2 patients) and the common flexor (n = 2 patients). Interobserver agreement for the entheses' thickness was as follows: intracorrelation coefficient class (ICC) of 0.86 (95% confidence interval [CI], 0.84–0.92) for the supraspinatus enthesis, ICC of 0.83 (95% CI, 0.83–0.90) for the common extensor enthesis, ICC of 0.96 (95% CI, 0.91–0.97) for the common flexor enthesis, and ICC of 0.94 (95% CI, 0.89–0.95) for the triceps enthesis. The κ index was 0.93 for the detection of the power Doppler signal. Intraobserver agreement was good for all evaluated entheses: ICC of 0.85 (95% CI, 0.83–0.91) for supraspinatus, ICC of 0.86 (95% CI, 0.84–0.91) for common extensor entheses, ICC of 0.89 (95% CI, 0.86–0.93) for common flexor entheses, and ICC of 0.96 (95% CI, 0.90–0.97) for evaluation of triceps entheses. The κ index was 0.91 for the detection of Doppler signal. Conclusions: The current study provides a comprehensive description of the structural appearance and vascularization of UL entheses on healthy children. This information can be useful as reference for interpretation of pathological findings in children with musculoskeletal diseases in clinical practice.